If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3a + b) + -6(2a + -3b) = 0 (3a * 2 + b * 2) + -6(2a + -3b) = 0 (6a + 2b) + -6(2a + -3b) = 0 6a + 2b + (2a * -6 + -3b * -6) = 0 6a + 2b + (-12a + 18b) = 0 Reorder the terms: 6a + -12a + 2b + 18b = 0 Combine like terms: 6a + -12a = -6a -6a + 2b + 18b = 0 Combine like terms: 2b + 18b = 20b -6a + 20b = 0 Solving -6a + 20b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-20b' to each side of the equation. -6a + 20b + -20b = 0 + -20b Combine like terms: 20b + -20b = 0 -6a + 0 = 0 + -20b -6a = 0 + -20b Remove the zero: -6a = -20b Divide each side by '-6'. a = 3.333333333b Simplifying a = 3.333333333b
| (n+1)*9=27q | | (n-4)*6=12 | | 148-2x=25x+19 | | 7-9x=83-23x | | x*x+7x=12 | | a*8+6=3 | | 8(x+2)=4(x+10) | | 4x-5=72-7x | | 152-10x=9x+19 | | 8x+5=3x+0 | | 11x+30=2x+300 | | 230-3x=42+20 | | 6x-9=-33-8x | | -3xy*2xy= | | 79-4x=8x-19 | | 6x^2-15x+8=0 | | x^2-8x+10=-2x+2 | | x^2-7x+15=9 | | 10x-17=14x-61 | | 3-t=3t+2 | | 1.3=5-3x-4-4x | | 5(x-2y)=2x+y | | -x^2+7x-11=0 | | 3-[-3+-7]=2 | | x^4-30x^2+221=0 | | 12=13x+7y | | (5-x)(3x+6)=0 | | 12x^3=15 | | 114-4x=14x+16 | | 83-5x=31x+23 | | 7x-x^2=11 | | 4x*-15x-4=0 |